Genetic polymorphisms of UTS2 rs2890565 Ser89Asn in cardiac hypertrophy in Chinese Han population - Zhao, Jing; Jiang, Jie; Wang, Jie; Liu, Lin; Han, Xiao-Ning; Chu, Song-Yun; Xue, Lin; Ding, Wen-Hui (Postgraduate medical journal, 2017)
ObjectiveCardiac hypertrophy is the heart's response to a variety of extrinsic and intrinsic stimuli, some of which might finally lead up to a maladaptive state. Clinical evidence, in vitro and in vivo studies have implicated urotensin II (U-II/UTS2) in the development of cardiac hypertrophy, contributing to the (patho)-physiological regulation of cardiovascular homeostasis in humans. Several genes are associated with left ventricular hypertrophy; considering these, our objective was to evaluate the possible role of UTS2 gene polymorphisms (Thr21Met and Ser89Asn) in the genetic susceptibility to cardiac hypertrophy in a Chinese population.MethodsA case-control study was designed to compare the distribution of alleles and genotypes between three groups: case group 1 (subjects with hypertension and cardiac hypertrophy, n=265), case group 2 (subjects with hypertension, without cardiac hypertrophy, n=768), and the control group (subjects neither with hypertension nor with cardiac hypertrophy, n=416). The detection of UTS2 gene polymorphisms was achieved with the PCR restriction fragment length polymorphism technique.ResultsWe did not identify statistically significant differences between the three groups, neither with regard to the frequency of genotype/variant at the Ser89Asn locus nor at the Thr21Met locus. When stratified by sex, differences in genotype distribution of polymorphism Ser89Asn were only seen in female subjects in both the additive tested inheritance model (OR=0.507, 95% CI 0.249 to 1.032, p=0.032) and the recessive tested inheritance model (OR=0.475, 95% CI 0.239 to 0.945, p=0.034) between case group 2 (subjects with hypertension, without cardiac hypertrophy) and the control group (subjects neither with hypertension nor with cardiac hypertrophy). When stratified by sex, for female subjects with cardiac hypertrophy, we identified statistically significant differences in left ventricular posterior wall thickness for variant genotypes at the Ser89Asn locus (AA vs GG: 1.2500 (1.2000, 1.3750) vs 1.2500 (1.2000, 1.3750), p=0.03) and (AG+AA vs GG: 1.2000 (1.2000, 1.3000) vs 1.2000 (1.1000, 1.2000), p=0.01).ConclusionsSer89Asn (S89N) polymorphisms of the UTS2 gene were associated with hypertension in a Chinese female population. Additionally, we demonstrated that genotype Asn89Asn was associated with left ventricular posterior wall thickness for subjects with hypertension and cardiac hypertrophy in a Chinese female population.